Synthesis and In Vitro Anticancer Evaluation of Flavone—1,2,3-Triazole Hybrids - Németh-Rieder Alexandra (MOLECULES, 2023)
Hybrid compounds of flavones, namely chrysin and kaempferol, and substituted 1,2,3-triazole derivatives, were synthesized by click reaction of the intermediate O-propargyl derivatives. 4-Fluoro- and 4-nitrobenzyl-1,2,3-triazole-containing hybrid molecules were prepared. The mono- and bis-coupled hybrids were investigated on 60 cell lines of 9 common cancer types (NCI60) in vitro as antitumor agents. Some of them proved to have a significant antiproliferative effect.